2021
DOI: 10.1021/acssuschemeng.0c09216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Butyl-Exchanged Polyoxymethylene Ethers as Renewable Diesel Blendstocks with Improved Fuel Properties

Abstract: Methyl-terminated polyoxymethylene ethers (MM-POMEs), having the formula CH 3 O−(CH 2 O) n −CH 3 (n = 3−5), are a high-cetane, low-sooting group of oxygenates that have recently attracted attention as potential diesel blendstocks. Despite these attractive fuel properties, MM-POMEs have shortcomings due to their low energy density and high water solubility. Guided by a computational fuel property assessment for POMEs with longer end-groups, the most promising improvements in the desired compression ignition fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Water solubility was approximated using a similar procedure to that previously published. 17 , 82 , 93 Each blendstock was added to DI water at a volumetric ratio of 1:5 and blended with a vortex mixer. The solution was allowed to separate for 24 h at ambient temperature (∼22°C).…”
Section: Methodsmentioning
confidence: 99%
“…Water solubility was approximated using a similar procedure to that previously published. 17 , 82 , 93 Each blendstock was added to DI water at a volumetric ratio of 1:5 and blended with a vortex mixer. The solution was allowed to separate for 24 h at ambient temperature (∼22°C).…”
Section: Methodsmentioning
confidence: 99%
“…As an example of this nomenclature, Figure 1 shows butoxymethoxymethoxybutane, which is here termed B-2-B. It is possible to produce nonsymmetric OMEs where X and Y are not the same; indeed, some of these molecules arise from the trans-acetalization reactions used in Arellano-Trevinõ et al's recent work 21 and make up part of the resultant tested mixture. However, this work focuses on symmetric OMEs to highlight the trends in properties from either alkyl group effects or chain length effects; asymmetric OMEs are beyond the intended scope of this work.…”
Section: ■ Nomenclature and Structuresmentioning
confidence: 99%
“…A past work by Murphy has shown that B-1-B has acceptable miscibility with diesel. 20 Additional works by Arellano-Trevinõ et al 21 and An et al 22 have considered the synthesis of, and measured some properties of, mixtures of butyl-terminated OMEs, but neither made any attempt to isolate and characterize individual components of their synthesis products. While these previous works demonstrate potential for improving the suitability of OMEs for fuel use by altering the alkyl terminations, there has not been a systematic study which varies both end group and oxymethylene chain length simultaneously to isolate influences of each alteration on the fuel properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…YSI requires orders of magnitude less sample volume than smoke point (100 μL versus 10 mL), which makes it useful for developing new fuel molecules. We have applied it to custom-synthesized alternative fuels such as dioxolanes and polyoxymethylene ethers where the available sample volumes were insufficient to measure smoke point [17,18].…”
Section: Introductionmentioning
confidence: 99%